44.7k views
2 votes
(3xy)^2x^4y simplifying an expression

1 Answer

4 votes

Answer:


36x^6y^3

Explanation:

The problem needs application of law of indices


1. (xy)^m = x^my^m

This means common power for terms can be applied to each term individually.


x^a x^b = x^(a+b)\\

Separate power for the terms having same base can be added together.

_______________________________________________________

we will be using these law of indices in the problem


(3xy)^2x^4y \\=> 3^2x^2y^2x^4y

applied the first rule of indices as mentioned above


3^2x^2y^2x^4y\\=>9*x^(2+4)4y^(2+1)\\=>9*4x^6y^3\\=>36x^6y^3

applied the second rule of indices as mentioned above

Thus, simplified form of (3xy)^2x^4y is
36x^6y^3.